The Impact of Nutrition Education Program upon Pregnant Mothers’ Nutritional Knowledge - Arkan B. Nagi (Iraqi National Journal of Nursing Specialties, 2023)
Objective: Determine the effectiveness of the Nutrition Education Program upon the pregnant mothers’ nutritional knowledge. Methodology: ٨ quazi-experimental study was carried out to determine the effectiveness of the nutrition education program upon the pregnant mother’s nutritional knowledge. A non-probability "purposive sample" of (60) pregnant mother was selected from Al-bayaa’ Primary Health Care Center in Baghdad City. These mothers were divided into two equal groups; study group and control group. A questionnaire was developed as a tool of data collection for the purpose of the study. A pilot study and follow-up was carried out to test the reliability and validity of the questionnaire for the period of Octoberl"2006 to July 12007. Data were analyzed through the application of descriptive and inferential statistical data analysis approaches. Results: The results of statistical data analysis revealed that the study group participants had benefits from the implementation of the nutrition education program and dramatic change had occurred in their nutritional knowledge. Recommendations: The study recommended that the nutrition education program can be presented to all pregnant mothers who are attending to the Primary Health Care Centers.